An Investigation of a Multiple-Measures Teaching Evaluation System and Its Relationship With Students' College-Going Outcomes. Issue 1 (January 2021) - Hughes, Rodney; Dahlin, Lauren; Tucci, Tara
In recent years, multiple-measures teaching evaluation systems have become widespread in states and school districts around the United States. Using administrative data from Pittsburgh Public Schools (PPS) and the National Student Clearinghouse, we examine the relationship between exposure to different ratings of teaching effectiveness in high school (based on a district-wide multiple-measures evaluation system) and high school graduation and college enrollment outcomes. We find a small but statistically significant difference in college enrollment rates for PPS graduates with more courses with teaching with the highest rating of Distinguished, and these students were also more likely to enroll in selective colleges.